Does gender of firm ownership matter? Female entrepreneurs and the gender pay gap - Alexander S. Kritikos; Mika Maliranta; Veera Nippala; Satu Nurmi (Journal of Population Economics, 2024)
Abstract We examine how the gender of business owners is related to the wages paid to female relative to male employees working in their firms. Using Finnish register data and employing firm fixed effects, we find that the gender pay gap is—starting from a gender pay gap of 11 to 12%—two to three percentage points lower for hourly wages in female-owned firms than in male-owned firms. Results are robust to how the wage is measured, as well as to various further robustness checks. More importantly, we find substantial differences between industries. While, for instance, in the manufacturing sector, the gender of the owner plays no role in the gender pay gap, in several service sector industries, like ICT or business services, no or a negligible gender pay gap can be found, but only when firms are led by female business owners. Businesses with male ownership maintain a gender pay gap of around 10% also in the latter industries. With increasing firm size, the influence of the gender of the owner, however, fades. In large firms, it seems that others—firm managers—determine wages and no differences in the pay gap are observed between male- and female-owned firms.
Additional information: J16;J24;J31;J71;L26;M13
Keywords: 330; Entrepreneurship; Gender pay gap; Discrimination; Linked employer-employee data